CYTOKINE PROFILE IN VISCERAL OBESITY AND ADVERSE CARDIOVASCULAR PROGNOSIS OF MYOCARDIAL INFARCTION - O. V. Gruzdeva; O. E. Akbasheva; V. G. Matveeva; Yu. A. Dyleva; E. I. Palicheva; V. N. Karetnikova; D. A. Borodkina; A. N. Kokov; T. S. Fedorova; O. L. Barbarash (Медицинская иммунология, 2015)
Presence of myocardial infarction in patients with obesity can lead to an uncontrolled increase in proinflammatory cytokines and unfavorable course of the pathological process. Objective: to study the relationship of key inflammatory factors and the development of complications at different terms after myocardial infarction in patients with visceral obesity. The study involved 94 men with myocardial infarction. Visceral obesity was diagnosed by multi-slice computed tomography (LightspeedVCT 64 ,General Electric,USA). On the 1st and 12th day of hospitalization, we determined serum concentrations of interleukins (TNFα, IL-1β, IL-6, IL-8 IL-10 and IL-12), and C-reactive protein. Adverse cardiovascular events were documented during the next year. The most informative indicators were identified by a stepwise logistic regression analysis. In patients with myocardial infarction an imbalance of cytokine profile revealed, i.e., an increase in proinflammatory markers (TNFα, IL-1β, IL-6, IL-8, IL-12, CRP), along with decrease in IL-10, being more pronounced in cases of visceral obesity. Among the studied markers, closest relationship was observed between visceral obesity and serum concentrations of IL-6 and CRP. Over the year, adverse cardiovascular events proved to be more frequent in patients with visceral obesity. Post-infarction complication risk was associated with higher concentrations of IL-6, IL-12 and IL-10 deficiency. Hence, development of adverse cardiovascular events within a year after myocardial infarction is more typical to the patients with visceral obesity, and is accompanied by activation of proinflammatory cytokines and IL-10 deficiency.